A Study of Intra-Operative and Post-Operative Complications among Smokers under General Anesthesia: An Hospital Based Study - Bharat Choudhary; Mahendra Kumar (Asian Journal of Medical Research, 2019)
Background: The link between smoking and complications is well documented across surgical specialities. Hence; the present study was undertaken for assessing Intra-Operative and Post-Operative Complications among Smokers under General Anesthesia.Subjects and Methods:The present study was undertaken in the department of Anaesthesia, Government Medical College, Barmer, Rajasthan, India with aim of assessing Intra-Operative and Post-Operative Complications among Smokers under General Anesthesia. A total of 50 patients were enrolled in the present study. Ethical approval was obtained from institutional ethical committee and written consent was obtained from all the patients after explaining in detail the entire research protocol. Inclusion criteria for the present study included: 1) Current smokers, 2) Patients with current smoking habit from a minimum of 5 years, 3) Patients scheduled to undergo any surgical procedure under general anesthesia. Complete demographic details of all the patients were obtained. Incidence of both intra-operative and postoperative complications in all the patients was recorded. All the results were recorded in Microsoft excel sheet and were analyzed by SPSS software.Results:Intra-operative complications included need for ventilator, heart attack and requirement of intra-operative analgesia. Postoperative complications included impaired wound healing and nausea and vomiting.Conclusion: Smokers are subjects to significant chances of occurrence of intra-operative and postoperative complications.